Solve the equation using the quadratic formula. x^2 + 2x – 3 Question Solve the equation using the quadratic formula. x^2 + 2x – 3 in progress 0 Math Piper 2 weeks 2021-10-07T13:20:38+00:00 2021-10-07T13:20:38+00:00 2 Answers 0

## Answers ( )

Answer:

Step-by-step explanation:

The given quadratic equation is expressed as

x² + 2x – 3 = 0

The equation is already in the standard form of ax² + bx + c

The general formula for solving quadratic equations is expressed as

x = [- b ± √(b² – 4ac)]/2a

From the equation given,

a = 1

b = 2

c = – 3

Therefore,

x = [- 2 ± √(2² – 4 × 1 × – 3)]/2 × 1

x = [- 2 ± √(4 – – 12)]/2

x = [- 2 ± √16]/2

x = (- 2 + 4)/2 or x = (- 2 – 4)/2

x = 2/2 or x = – 6/2

x = 1 or x = – 3

x²+2x-3

x²+3x-x-3

x(x+3)-1(x+3)

(x+3)(x-1)

x=-3,1